Gay rights vs. religious liberty? : the unnecessary conflict - Koppelman, Andrew (New York : Oxford University Press, 2020)
Should religious people who conscientiously object to facilitating same-sex weddings, and who therefore decline to provide cakes, photography, or other services, be exempted from antidiscrimination laws? This issue has taken on an importance far beyond the tiny number who have made such claims. Gay rights advocates fear that exempting even a few religious dissenters would unleash a devastating wave of discrimination. Conservative Christians fear that the law will treat them like racists and drive them to the margins of American society. Both sides are mistaken. This is not a matter of abstract principle, and none of the constitutional claims work. This is an appropriate occasion for legislative negotiation. This book is a systematic accounting of the interests that must be balanced in any decent compromise, in terms that both sides can recognise and appreciate.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 27, 2020).
Keywords: Freedom of religion -- United States; Gay rights -- United States -- Religious aspects